2006
DOI: 10.1038/nature05378
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 regulates erythropoiesis by preventing caspase-3-mediated cleavage of GATA-1

Abstract: Caspase-3 is activated during both terminal differentiation and erythropoietin-starvation-induced apoptosis of human erythroid precursors. The transcription factor GATA-1, which performs an essential function in erythroid differentiation by positively regulating promoters of erythroid and anti-apoptotic genes, is cleaved by caspases in erythroid precursors undergoing cell death upon erythropoietin starvation or engagement of the death receptor Fas. In contrast, by an unknown mechanism, GATA-1 remains uncleaved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
243
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(257 citation statements)
references
References 24 publications
9
243
1
4
Order By: Relevance
“…GATA-1 cleavage by caspase-8 was proposed to have an important role in the negative control of erythropoiesis (De Maria et al, 1999)), whereas GATA-1 was protected from differentiation-associated activation of caspase-3 by interaction with HSP70 (Ribeil et al, 2007). HSP70 expression is increased in breast carcinomas (Ciocca and Calderwood, 2005) and could protect GATA-1 from degradation in transformed cells when caspases are activated.…”
Section: Discussionmentioning
confidence: 99%
“…GATA-1 cleavage by caspase-8 was proposed to have an important role in the negative control of erythropoiesis (De Maria et al, 1999)), whereas GATA-1 was protected from differentiation-associated activation of caspase-3 by interaction with HSP70 (Ribeil et al, 2007). HSP70 expression is increased in breast carcinomas (Ciocca and Calderwood, 2005) and could protect GATA-1 from degradation in transformed cells when caspases are activated.…”
Section: Discussionmentioning
confidence: 99%
“…As an E3 ligase, c-IAP1 could favour the degradation of specific proteins. Caspases have been reported to be ubiquitinated by mammalian IAPs in vitro but the role of these enzymes in cell differentiation is limited to specific cell types 33,34 and evidence that IAPs physiologically ubiquitinylate caspases and promote their degradation, is still missing. 32 c-IAP1 could also modulate NF-kB transcription factor activity 9 or specific signalling pathways involving adaptor molecules such as TRAF2 7 and serine-threonine kinases such as ASK1.…”
Section: Discussionmentioning
confidence: 99%
“…acinus), but spares other potential substrates (such as the major erythroid transcription factor GATA-1), presumably Day jobs of night killers L Galluzzi et al because these proteins are protected by the interaction with HSP70. 19,20 Interestingly, it has been suggested that caspase-3 involvement in erythropoiesis is restricted to the early phases of proerythroblast differentiation, with no major roles in the nuclear substructure reorganization and nuclear extrusion that characterize the late phases of the process. 21 Caspase activation is also involved in thrombopoiesis.…”
Section: Vital Functions Of Mammalian Caspasesmentioning
confidence: 99%